STRATEGI PENGEMBANGAN USAHA KULINER - Irvina Safitri; Darmawan Salman; Rahmadani Rahmadani (Jurnal Sosial Ekonomi Pertanian, 2018)
Lemang is one of traditional food made from raw material of sticky rice (black and white) wrapped with banana leaf and put into bamboo container from Bangkala Subdistrict, Jeneponto Regency. This study aims to: (1) Describe the strategy in maintaining relationships with providers Lemang Dg Awing in District Bangkala (2) Describe the strategy in maintaining the relationship with the business of Lemang Dg Awing. (3) Describe the strategy in maintaining the quality of lemang in the business of Lemang Dg Awing. (4) Analyzing the business continuity hole in the case of Lemang Dg Awing business. This study used qualitative descriptive, participatory analysis tools and in-depth interviews, with research locations in Bangkala District, Jeneponto Regency, South Sulawesi. The results concluded that: 1. Strategy built by Dg. Awing with suppliers With suppliers for suppliers Invites suppliers to make events, Presents lemang to suppliers. Provide additional bonus through channeling for purchases of lemang 2. Dg Awing always maintains relationships  with  its  employees  such  as:  Always  work  in  the morning,  Invites employees at the time of the event, Provides support during times of big days, Provides money support, Prepares cold food and drinks on the part burning, especially during the day, Inviting vacation together. 3. Dg Awing Always pay attention to 6 basic components to maintain the quality of lemang remain stored, such as aroma, shape, size, taste, texture and color lemang 4. Dg. Awing continues to control 3 aspects for business continuity related to raw material suppliers, Maintain and maintain good relationships to its workers. Keep maintaining the quality of the lemang itself to continue to increase sales volume and increase consumer loyality in buying lemang.Keywords: lemang; traditional food; development strategy.